(untitled) (SCIÉNDO INGENIUM, 2024)
An analysis of the hearing risk was carried out in the Mining Management Engineering laboratory of the UPC - Chorrillos, in the first stage of the investigation the noise level of 9 pieces of equipment in the laboratory was evaluated, finding that the jaw crusher, disc pulverizer , ball mill, extractor and core cutter exceed the LMP with averages of 90.61, 91.13, 92.18, 92.68, and 89.89 dB, respectively. In the second stage, the noise dose was monitored in 6 people, in the laboratory and 4 adjacent areas, revealing that the members of the laboratory were exposed to 87.21 and 86.64 dB, exceeding the LMP, the surrounding rooms showed exposures of 31.87, 32.78, 30.72, and 29.29 dB in the administrative office. In the third stage, a survey was conducted with 87 people indicating that 14% perceived the noise from the equipment as constant and continuous, 100% of the teachers, 80% of the administrative staff and 73% of the students feel discomfort due to the noise. noise in their work areas and 25% of respondents experienced physical discomfort due to noise.